2021
DOI: 10.3390/ijerph18115926
|View full text |Cite
|
Sign up to set email alerts
|

Combined Effects of Wildfire and Vegetation Cover Type on Volcanic Soil (Functions and Properties) in a Mediterranean Region: Comparison of Two Soil Quality Indices

Abstract: Mediterranean regions are the most impacted by fire in Europe. The effects of fire on soil greatly vary according to several factors such as vegetation cover type, but they are scarcely studied. Therefore, this research aimed at evaluating the combined impacts of fire and vegetation on single soil characteristics and on the overall soil quality and functionality through two soil quality indices, simple additive (SQI) and a weighted function (SQIFUNCT). In order to reach the aims, burnt and unburnt soils were c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 51 publications
0
9
0
Order By: Relevance
“…In fact, the intensity of management practice modified the accumulation of soil nutrients and pollutants, influencing the abundance and the activities of organisms [21]. Moreover, the vegetation cover had a direct effect on soil properties, increasing the organic matter content, changing the rhizosphere pH, modifying the mobility of soil elements, which, in turn, results in a high soil biodiversity and quality [16,29].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, the intensity of management practice modified the accumulation of soil nutrients and pollutants, influencing the abundance and the activities of organisms [21]. Moreover, the vegetation cover had a direct effect on soil properties, increasing the organic matter content, changing the rhizosphere pH, modifying the mobility of soil elements, which, in turn, results in a high soil biodiversity and quality [16,29].…”
Section: Discussionmentioning
confidence: 99%
“…Because of the growing public interest in sustainability and the desire to determine effects of land use and management practices on soil resources, one of the most important goals for modern soil science is to understand and assess soil quality [26]. One way to integrate information from soil indicators into the management decision process is the use of a soil quality index, as a primary indicator of sustainable land management [27][28][29].…”
Section: Introductionmentioning
confidence: 99%
“…The fire impact on soil microbial communities and their recovery rates might be also mediated by soil properties [25] and by plant-soil interactions [26,27]. In fact, bacteria are stimulated in soils covered by vegetation, that enhances water permeability and organic matter content, as compared to those in bare soils [28], and both symbiotic and saprophytic fungi are impacted by post-fire plant communities [29].…”
Section: Introductionmentioning
confidence: 99%
“…forest landscapes in southern Chile and Argentina [1][2][3]. Wildfires profoundly impact soil properties [4], mostly by altering the thickness, extent and composition of soil organic matter (SOM) [5][6][7][8]. During a fire, the SOM may be affected differently at each mineral soil horizon.…”
Section: Introductionmentioning
confidence: 99%
“…If ligno-cellulosic-rich material is burnt, a considerable part of the aromatic C derives from carbohydrates, which are dehydrated and subsequently aromatized [15,16]. It has been shown that the extent of this phenomenon increases with the increasing soil temperatures reached during wildfires [8]. A fire-induced alteration is expected to have a long-term impact on the quality and quantity of different SOM fractions, since above-and belowground fresh C input is the main primary source of carbohydrates in the soil, and it represents a major energy source for microbial growth [17].…”
Section: Introductionmentioning
confidence: 99%